MAIN FEATURES OF QUALITATIVE LEARNING SPACE AND PRE-SCHOOL CHILDREN LANGUAGE DEVELOPMENT - Tauriņa, Agrita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The main goal of ongoing transformation of the Latvian pre-school education system is competence-based approach. The essence of this approach is to promote functionality, integrity and practical application of knowledge, explanation of the surroundings, universality of skills, creativity, problem solving. Modern society requests not only for teacher to demonstrate enthusiasm by sharing a deep level of content knowledge, but also necessity of learning space which focus on sensorial senses. It is a way of learning through doing, the process when children obtain knowledge and skills via personal experience, like being creative, flexible, able to analyse, think critically etc. The aim of this article is to analyse successfully created learning space and language development for pre-school age children based on literature analysis and adapted survey results. The empirical study, which took place in Riga, examines these two aspects in pre-school children development of language, communication and the prerequisites of reading and writing. The Latvia State Research Program “Latvian language” No. VPPIZM-2018/2-0002 researchers find out that children who attend minority pre-school education programme have insufficient support in Latvian language environment. Results, conclusions. Qualitative learning space promotes learning abilities and responsible attitudes. This important condition needs to be implemented in competence-based approach to see improvements in pre-school children language and communication development.